2001
DOI: 10.1248/bpb.24.978
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modification of the Carboxyl Groups of the Sialic Acid Binding Lectin from Bullfrog (Rana catesbeiana) Oocyte on Anti-tumor Activity.

Abstract: The sialic acid binding lectin from Rana catesbeiana oocyte (cSBL) is known to have anti-tumor activity.2) cSBL is a multifunctional protein which has pyrimidine base specific ribonuclease activity. 3,4) In respect to RNase, cSBL belongs to the RNase A family, and is a very heat stable enzyme. It remained 100% active after heating at 100°C. 3,5) Four RNases belonging to the RNase A family have been isolated from Rana family frogs to date. Their primary structures are shown in Fig. 1. They have anti-tumor activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…In the previous report, 12) we reported that a chemically modified form of cSBL with a higher positive net charge was internalized more effectively into P388 cells than the native cSBL. Therefore, we investigated the relative rate of internalization of the mutant cSBLs.…”
Section: Effect Of Mutations On Internalization Efficiencymentioning
confidence: 73%
See 3 more Smart Citations
“…In the previous report, 12) we reported that a chemically modified form of cSBL with a higher positive net charge was internalized more effectively into P388 cells than the native cSBL. Therefore, we investigated the relative rate of internalization of the mutant cSBLs.…”
Section: Effect Of Mutations On Internalization Efficiencymentioning
confidence: 73%
“…The results of this report were qualitatively consistent with similar experiments in which the acidic amino acid residues of cSBL were modified chemically with EDC-ethylenediamine. 12,13) The substitutions of E97 with arginine and glutamine most affected the enzymatic activities of cSBL, when RNA was the substrate. This may be due to the fact that E97 is one of the constituents of the B2 base recognition site of the RNase A superfamily, and is conserved in the RNase A superfamily, although we do not know the exact location of this group in the substrate analoguecSBL complex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The location of the acidic amino acid residues in the primary structure modified with EDC has yet to be determined. 5) To elucidate the fundamental mechanism by which antitumor activities enhanced, we investigated the RNase activity of the modified cSBL. We focused on the effects of modification on double stranded RNase activity and the base specificity of the modified cSBL.…”
mentioning
confidence: 99%